A Block Diagram of Electromagnetoelastic Actuator for Control Systems in Nanoscience and Nanotechnology - Afonin, S. M. (Transactions on Engineering and Computing Sciences, 2020)
The block diagram and the transfer functions of the electromagnetoelastic actuator are received for control systems in nanoscience and nanotechnology. The block diagram of the electromagnetoelastic actuator is reflected the transformation of electrical energy into mechanical energy, in contrast to Cady’s and Mason’s electrical equivalent circuits of piezotransducer. The electromagnetoelasticity equation and the second order linear ordinary differential equation with boundary conditions are solved for calculations the block diagram of the electromagnetoelastic actuator. The block diagram of the piezoactuator is obtained with using the reverse and direct piezoelectric effects. The back electromotive force is determined from the direct piezoelectric effect equation. The transfer functions of the piezoactuators are obtained for control systems in nanoscience and nanotechnology.